2020
DOI: 10.1093/rheumatology/keaa576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of baricitinib in patients with moderate-to-severe rheumatoid arthritis with 3 years of treatment: results from a long-term study 

Abstract: Objective To evaluate the long-term efficacy of once-daily baricitinib 4 mg in patients with active RA who were either naïve to DMARDs or who had inadequate response (IR) to MTX. Methods Analyses of data from two completed 52-week, phase III studies, RA-BEGIN (DMARD-naïve) and RA-BEAM (MTX-IR), and one ongoing long-term extension (LTE) study (RA-BEYOND) were performed (148 total weeks). At week 52, DMARD-naïve patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Most patients also maintained at least LDA, as assessed with the SDAI. This observation is similar to a previous report on RA-BEYOND (up to 3 years) of SDAI LDA data from patients originating in RA-BEGIN and RA-BEAM originally treated with or switched to baricitinib (13,20). Thus, these patients had both important clinical responses and marked decreases in radiographic progression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most patients also maintained at least LDA, as assessed with the SDAI. This observation is similar to a previous report on RA-BEYOND (up to 3 years) of SDAI LDA data from patients originating in RA-BEGIN and RA-BEAM originally treated with or switched to baricitinib (13,20). Thus, these patients had both important clinical responses and marked decreases in radiographic progression.…”
Section: Discussionsupporting
confidence: 90%
“…For SDAI ≤11, nonresponder imputation, in which discontinued patients were considered nonresponders, and completer analyses, based on patients with data available at the analysis time point, were performed. Data collected from patients originally treated with baricitinib 4 mg who received baricitinib 2 mg in the dose step-down substudy of the LTE were imputed based on data from patients in the substudy who remained on baricitinib 4 mg, using previously reported methods (20).…”
Section: Statistical Analysis the Analysis Population Included Patients Who Had Available Baseline Radiographicmentioning
confidence: 99%
“…Since generic tsDMARDs are cheaper and oral, we recommend them before bDMARDs (Figure 1 ). Despite the excellent initial response, secondary treatment inefficacy can occur with anti-TNF and other biologics (due to anti-drug antibodies) [ 49 ]. The secondary loss of treatment efficacy has not yet been observed with the tsDMARDs [ 49 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, Smolen et al completed a long‐term study of three years of once‐daily baricitinib 4 mg in patients with moderate‐to‐severe RA, who had inadequate response to methotrexate (MTX‐IR), or were naïve to biologic disease‐modifying anti‐rheumatic drugs (DMARDs). A total of 3770 patients from two completed 52‐week, phase 3 studies, and one long‐term extension study (148 weeks) were performed to assess disease activity clinical remission and physical functioning were assessed 69 . After 148 weeks across all groups, 3.6% discontinued baricitinib due to lack of efficacy and 10.7% discontinued baricitinib due to adverse events 69 .…”
Section: Long‐term Usementioning
confidence: 99%
“…A total of 3770 patients from two completed 52‐week, phase 3 studies, and one long‐term extension study (148 weeks) were performed to assess disease activity clinical remission and physical functioning were assessed 69 . After 148 weeks across all groups, 3.6% discontinued baricitinib due to lack of efficacy and 10.7% discontinued baricitinib due to adverse events 69 . Overall, baricitinib 4 mg treatment demonstrated efficacy for up to 3 years and was well tolerated.…”
Section: Long‐term Usementioning
confidence: 99%